2015
DOI: 10.4049/jimmunol.1500409
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatitis C Virus Sensing by Human Trophoblasts Induces Innate Immune Responses and Recruitment of Maternal NK Cells: Potential Implications for Limiting Vertical Transmission

Abstract: Hepatitis C virus (HCV) is the world’s most common blood-borne viral infection for which there is no vaccine. The rates of vertical transmission range between 3–6% with odds 90% higher in the presence of HIV co-infection. Prevention of vertical transmission is not possible due to lack of an approved therapy for use in pregnancy or an effective vaccine. Recently, HCV has been identified as an independent risk factor for pre-term delivery, perinatal mortality and other complications. In this study, we characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 61 publications
(83 reference statements)
1
34
0
Order By: Relevance
“…4 and 5). The authors further demonstrated the presence of HCV NS5A protein, a nonstructural HCV protein, within human trophoblast cells, suggesting endocytosis and uptake of HCV 2. This was a meticulously designed study, which effectively demonstrated this mechanism of transmission.…”
Section: Hcvmentioning
confidence: 88%
“…4 and 5). The authors further demonstrated the presence of HCV NS5A protein, a nonstructural HCV protein, within human trophoblast cells, suggesting endocytosis and uptake of HCV 2. This was a meticulously designed study, which effectively demonstrated this mechanism of transmission.…”
Section: Hcvmentioning
confidence: 88%
“…Finally, the host animals were F/R mice that lacked mature T and B cells but retained both natural killer cells and macrophages. The natural killer cells were regarded as first‐line effectors of the innate immune response and played a distinct role against HCV infection . The loss of HCV from engrafted hHBs could be due partially to the existing innate immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…The natural killer cells were regarded as first-line effectors of the innate immune response and played a distinct role against HCV infection. (15,44) The loss of HCV from engrafted hHBs could be due partially to the existing innate immune cells. In future, we will improve the hESC-derived HBs engrafted mouse model through removing natural killer cells by antibody treatments along with other forms of immunosuppression for susceptibility or enhanced HCV replication.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the interaction of dNK cells with HLA-E and HLA-G molecules expressed by extravillous trophoblast has been shown to be critically involved in the inhibition of dNK cell cytolytic functions during normal pregnancy [119,136]. Notably, the recent findings that human trophoblast cells promote the activation and cyotoxicity of dNK cells upon hepatitis C virus sensing [138] clearly indicate that NK cells at the feto-maternal interface can switch their phenotype in case of infection and suggest a possible involvement of these cells in the pathogenesis of PTB.…”
Section: Nk Cellsmentioning
confidence: 99%